Test report no. PLBO/11 comparison of PERPRO grade WK8/T0354 against grade CLV when machining Meehanite - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
Tools of grade 14K8/T0354 and CLV were tested at 300 f.p.m. cutting speed, 0.10 in. depth of cut and 0.010 in/rev. feed to 0.030 in. flankwear. The two bars of Meehanite used for the tests gave different results but in each case the performance of CLV was slightly better than that of WK8/T0354; this difference was more pronounced with the less easy to machine material.